Análise comparativa de alteração de cor em protocolos de clareamento dental: revisão sistemática e network metanálise - Oliveira, Murilo Navarro de (2020)
Objectives: Looking after clinical randomized trials that compare different protocols of teeth whitening, to evaluate which methods presents the best results of color change. Methods: Nine databases were used, including part of the gray literature”. The whitening methods were divided in four groups (In-Office, At-home, Combined and Whitestrips) and grouped according to each whitening agent, material concentration and action time. Data extraction and risk of bias assessment were performed and the values of ∆Eab were collected in four times after treatment (immediately after, seven days, 30 days and 180 days). Network was performed to indirectly compare color change of bleaching protocols. Different analyses were performed for each follow-up, and the comparisons were not equal over the different time points. Results: 19 clinical trials with at least one common group with other studies were included in the meta-analysis. The results immediately after were divided in two analysis with no common comparator and the exclusively in-office protocols presents worse results of color change compared to other techniques. After seven days, the analysis shows better values of ∆Eab for a combined technique. The 30 days after analysis were divided in three parts with no relation between them and at-home or combined protocols related higher degree of color change, in-office techniques did not show statistical difference among them. And the results of 180 days were limited to four protocols, and an at-home technique were better than other three in-office methods. Conclusions: Exclusively In-Office techniques presented worse results of color change compared to other techniques.